Bactérias endofíticas em sementes de Castanha-do-Brasil - Sindô, Jéssica Carvalho (2017)
Brazil nut, Bertholletia excelsa H. B. K., is a species native to the Amazon that stands out in regional agribusiness because it is a product of economic importance in the national and international market. It has high nutritional value, besides the exotic flavor, which guarantees its use and commercialization in several food sectors. However, the climatic conditions in which this species is inserted favor the contamination by mycotoxin-producing fungi. Despite the importance of mycotoxins in nuts, there are endophytic microorganisms that have several biotechnological potential, including the production of antimicrobial compounds. In this sense, the present study aimed to: i) evaluate the diversity of endophytic bacteria in Brazil nut seeds; ii) to study the antagonistic potential of endophytic bacteria to a mycotoxin-producing fungus and an opportunistic soil pathogen. In order to do so, we analyzed nut seeds of two groups: purchased in local commerce and collected from planting with grafting. Both underwent superficial disinfection for the isolation of endophytic microorganisms, analyzing films and almonds, separately. These bacteria were identified by partial sequencing analysis of the 16S rDNA gene and submitted to the test of antagonism to fungi Rhizoctonia sp. and Aspergillus sp. by matched culture method. A total of 89 bacteria, Bacillus, Acinetobacter, Streptomyces, Hephaestia, Bordetella, Amycolatopsis, Microlunatus, Microbacterium, Brevundinomonas, Conhella, Rhizobium, Sinomonas, and Oxalicibacyerium were isolated as endophytic seeds of Brazil nut. Of which the species Bacillus and Streptomyces predominated as to the antagonistic activity to the fungi tested.